GLYCEMIC HOMEOSTASIS OF SMALL AND NORMAL LITTER DURING RAT ADOLESCENCE - Rodrigues Raposo, Scarlett; Paulo Jacinto Saavedra, Lucas; Natália Chimirri Peres, Maria; Pereira Lopes, Rafael; Vinícius Martins, Marcos; Lima dos Santos, Filipe; Nascimento de Souza Rodrigues, Willian; Debossan Fernandes, Maryana; Narciso Constancio, Mariana; Kian Guimaraes Lopes, Gabriel; Ferreira Barbosa, Letícia; Lomes da Cruz, Kérolym; et al. (Arquivos do Mudi, 2023)
Childhood obesity has become a public health concern, as it leads to cardiometabolic disorders. The Developmental Origins of Health and Disease (DOHaD) concept shows that insults in critical windows of development can program the individual for both health and disease. In the neonatal supernutrition model, known as small litter (SL), the litter is reduced to 3 animals per dam, mimicking obesity, while the normal litter (NL) control animals have only 9 animals per dam. The period of adolescence in SL animals is still little explored, it is known that in this phase there are many hormonal changes, but it is still not known how the behavior is in relation to glycemia, so our objective was to evaluate glycemia during the tolerance test oral glucose in NL and SL animals during adolescence. It is observed that the NL and SL animals show no difference in glucose tolerance at 45 and 60 days. However, both groups are glucose intolerant when compared to their respective controls in adult life. We conclude that there is glucose intolerance during adolescence regardless of the nutritional insult.